Pembacaan Heuristik dan Hermeneutik Puisi “Tak Ada Signal” Karya Dinullah Rayes - Jumianti Diana (Ruang Kata, 2026)
This study aims to reveal the meaning contained in the poem entitled “Tak Ada Signal” (No Signal) by Dinullah Rayes using Riffaterre's semiotic theory, namely heuristic reading and hermeneutic reading. The research method used is descriptive qualitative research. Data collection was carried out through literature review techniques, namely observation and note-taking. Data analysis was carried out using the descriptive analytical method. The results show that the poem conveys the meaning of a person's lack of response to the guidance they experience. This occurs as a result of the heart being enveloped in darkness, making it insensitive to the whispers of the Most Merciful God. Humans who are still alive physically but have lost their inner sensitivity. They can still see, hear, and speak, but their hearts are no longer sensitive to the truth. He should realize that death is inevitable and that the existence of the afterlife is something that cannot be known with certainty. The poet's introspective attitude reflects that mistakes or evil are not attributed to one person alone, but are possibilities that exist within every human being. Sometimes humans are arrogant and stray from divine values. This indicates a closed state of mind. Thus, awareness of divine guidance cannot remind and accept deep love in the heart. So, the poem actually invites readers to cleanse and soften their hearts so that divine love and light can return to their hearts. Because the obstacle to the relationship between humans and God is not the absence of guidance or light from the divine, but rather the human heart itself, which is too hard and closed